Assessment of Real-Time RT-PCR Kits for SARS-CoV-2 Detection - Okamaoto, Kiyoko; Shirato, Kazuya; Nao, Naganori; Saito, Shinji; Kageyama, Tsutomu; Hasegawa, Hideki; Suzuki, Tadaki; Matsuyama, Shutoku; Takeda, Makoto (Japanese Journal of Infectious Diseases, 2020)
The coronavirus induced disease 2019 (COVID-19) outbreak caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Wuhan (China) in December 2019 is currently spreading rapidly worldwide. We recently reported a laboratory protocol for the diagnosis of SARS-CoV-2 based on real-time reverse transcriptase PCR (RT-PCR) assays using two primer sets, N and N2. On January 30–31, 2020, the protocol and the reagents for these assays were distributed to the local public health institutes and quarantine depots in Japan nationwide, and thereafter SARS-CoV-2 diagnostic testing was initiated. For further validation, the assays were compared with the commercially available kits using the SARS-CoV-2 viral RNA and clinical specimens obtained from COVID19-suspected individuals. The LightMix Modular SARS and Wuhan CoV E-gene (LM S&W-E) assay was highly sensitive for the SARS-CoV-2, as was the N2 set, as both the assays showed consistent results for the clinical specimens. While the LM S&W-E set targets the highly conserved region of E gene in the SARS-CoV and SARS-CoV-2, the N2 set was designed to target specifically the unique region in the SARS-CoV-2 N gene. Therefore, the N2 set exhibits high specificity and sensitivity for SARS-CoV-2 detection. These results indicate that the protocol using the N and N2 sets is comparable to the commercially available kits, and thus is reliable for laboratory diagnosis of COVID-19.